Thermistor paste and preparation method thereof

The thermistor paste obtained by mixing the sintered thermistor semi-finished slurry, glass powder and organic carrier can solve the lack of mechanical strength, high production cost and electrical stability of the thermistor paste in the prior art. The poor problem has achieved improvements in electrical stability and mechanical strength and reduced production costs.

CN119480303APending Publication Date: 2025-02-18YAGEO ELECTRONICS CHINA CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310996084.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing thermistor paste has problems such as insufficient mechanical structure strength, high production cost, and poor powder dispersion and electrical stability of the paste.

Method used

The thermistor paste is prepared by mixing the thermistor semi-finished slurry with glass powder and organic carrier. The thermistor semi-finished slurry is sintered to ensure electrical stability and does not contain precious metals such as ruthenium, gold or platinum , reduce production costs.

Benefits of technology

The electrical stability and mechanical strength of the thermistor paste are improved, while reducing production costs and enabling rapid production of thermal-sensitive blocking wafers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480303A_ABST
    Figure CN119480303A_ABST
Patent Text Reader

Abstract

The invention relates to thermistor paste and a preparation method thereof. The thermistor paste comprises a specific content of thermistor powder, glass powder and an organic carrier, wherein the organic carrier comprises an organic solvent, a binder and an additive. The thermistor semi-finished product slurry is sintered, so that the thermistor semi-finished product slurry has relatively uniform electrical characteristics and relatively good electrical stability. The thermistor paste does not contain noble metals such as ruthenium, gold or platinum, so that the production cost can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermistor paste and a method for making the thermistor paste, and in particular to a thick film thermistor paste made by mixing thermistor semi-finished product slurry with glass powder and an organic carrier. Background Art

[0002] In the field of thermistors, thermistor crystals can be formed by stacking layers or co-firing with silver electrodes. However, stacking sintering is prone to sintering shrinkage and lamination separation, and the resulting product has poor mechanical structural strength, which is not conducive to the bending or vibration of the circuit board.

[0003] Currently, a thermistor paste formed by thick film printing is known, which is formed by mixing powder, ruthenium oxide, glass powder and colloid. However, ruthenium is a precious metal, so the production cost is relatively high. In addition, the thermistor paste has the problems of paste powder dispersion and electrical stability.

[0004] In view of the above, there is still a need to provide a thermistor paste and a method for making the thermistor paste that can solve the above problems. Summary of the invention

[0005] The present invention provides a thermistor paste and a method for making the same. The thermistor paste of the present invention is prepared by mixing a thermistor semi-finished product slurry with glass powder and an organic carrier, wherein the thermistor semi-finished product slurry is sintered, so that the prepared thermistor paste has more uniform electrical properties and better electrical stability. The thermistor paste of the present invention does not contain precious metals such as ruthenium, gold or platinum, so the production cost can be reduced. In addition, the thermistor paste of the present invention can be used in a thick film printing method to quickly produce thermistor interrupter chips.

[0006] The present invention provides a thermistor paste, which comprises 50 to 89 weight percent of thermistor powder, 1 to 5 weight percent of glass powder, and 10 to 45 weight percent of an organic carrier, based on the total weight of the thermistor paste being 100 weight percent. The main component of the thermistor powder is Mn x Co 1-x Ni y O 1.6 , x is 0.4 to 1.0, y is 0.07 to 0.75. Based on the total weight of the organic vehicle being 100 weight percent, the organic vehicle comprises 80 weight percent to 92 weight percent of an organic solvent, 5 weight percent to 15 weight percent of a binder, and 3 weight percent to 5 weight percent of an additive, wherein the average grinding fineness of the thermistor paste is less than 20 μm.

[0007] In some embodiments, the glass powder contains 20 to 50 weight percent of Bi2O3, 10 to 30 weight percent of SiO2, 5 to 30 weight percent of B2O3, 5 to 10 weight percent of TiO2, 5 to 20 weight percent of Al2O3, 5 to 20 weight percent of ZnO, and 5 to 20 weight percent of V2O5, based on the total weight of the glass powder as 100 weight percent.

[0008] In some embodiments, the organic solvent is selected from the group consisting of ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, hexanol, terpineol, benzyl alcohol and petroleum hydrocarbons.

[0009] In some embodiments, the organic solvent does not include methanol and ethanol.

[0010] In some embodiments, the binder is selected from the group consisting of ethyl cellulose, methyl cellulose, rosin, polymethacrylic acid amine and polyvinyl butyral.

[0011] In some embodiments, the additive is selected from the group consisting of lecithin, oleic acid, stearic acid, fatty acids, erucamide, oleamide, stearamide, polyacrylamide, and vinyl bisstearamide.

[0012] In some embodiments, the viscosity of the thermistor paste is 5 Pa·s to 300 Pa·s.

[0013] The present invention provides a method for making a thermistor paste, comprising the following operations. A thermistor semi-finished product slurry is provided. Glass powder is provided. An organic carrier is provided, wherein the organic carrier comprises an organic solvent, a binder and an additive. The thermistor semi-finished product slurry, the glass powder and the organic carrier are mixed to obtain a thermistor semi-finished product slurry mixture, wherein the thermistor semi-finished product slurry mixture comprises 40 to 70 weight percent of the thermistor semi-finished product slurry, 1 to 5 weight percent of glass powder, 10 to 40 weight percent of an organic solvent, 5 to 15 weight percent of a binder and 0.5 to 5 weight percent of an additive, based on the total weight of the thermistor semi-finished product slurry mixture as 100 weight percent. The thermistor semi-finished product slurry mixture is rolled using three rollers. After rolling the thermistor semi-finished product slurry mixture using three rollers, the thermistor semi-finished product slurry mixture is filtered to obtain a thermistor paste.

[0014] In some embodiments, the preparation of the thermistor semi-finished product slurry includes the following operations: providing a thermistor sintered product. mixing the thermistor sintered product, pinene alcohol, and oleamide to obtain a thermistor sintered product mixture, wherein the thermistor sintered product accounts for 40 to 60 weight percent, pinene alcohol accounts for 40 to 55 weight percent, and oleamide accounts for 0.5 to 5 weight percent based on the total weight of the thermistor sintered product mixture as 100 weight percent. ball milling the thermistor sintered product mixture to obtain the thermistor semi-finished product slurry.

[0015] In some embodiments, the sintering temperature of the thermistor paste is 650°C to 1100°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Various aspects of the present disclosure are best understood from the following detailed description when read in conjunction with the accompanying figures.

[0017] Figure 1 FIG. 4 is a flow chart of a method for manufacturing a thermistor paste according to some embodiments of the present disclosure. DETAILED DESCRIPTION

[0018] The manufacture and use of embodiments of the present invention are discussed in detail below. However, it is to be understood that the embodiments provide many applicable inventive concepts that can be implemented in a variety of specific contexts. The specific embodiments discussed are for illustration only and are not intended to limit the scope of the present invention.

[0019] In this article, the range expressed by "a value to another value" is a summary expression method that avoids listing all the values ​​in the range one by one in the specification. Therefore, the description of a specific numerical range covers any value in the numerical range and a smaller numerical range defined by any value in the numerical range, just as if the arbitrary value and the smaller numerical range were written in the specification. As used herein, the term "and / or" includes any and all combinations of one or more related listed items.

[0020] Although a series of operations or steps are used below to illustrate the methods disclosed herein, the order in which these operations or steps are shown should not be construed as a limitation of the present disclosure. For example, certain operations or steps may be performed in different orders and / or simultaneously with other steps. In addition, it is not necessary to perform all of the operations, steps, and / or features illustrated to achieve an embodiment of the present disclosure. In addition, each operation or step described herein may include several sub-steps or actions.

[0021] The present invention provides a thermistor paste made by using a thermistor semi-finished product slurry (also called NTC (negative temperature coefficient) thermistor semi-finished product slurry) and glass powder and an organic carrier, wherein the thermistor semi-finished product slurry is made by using Figure 1 The flow chart 100 shown is obtained.

[0022] Please refer to Figure 1 , first calcining the element powder at 600 to 950° C. for 1 to 4 hours, as shown in block 110. The element powder includes manganese tetraoxide (Mn3O4), cobalt tetraoxide (Co3O4) and nickel trioxide (Ni2O3).

[0023] Then, the above-mentioned element powders are uniformly mixed to obtain a negative temperature coefficient (NTC) thermistor mixture, as shown in block 120. In some embodiments, based on the total weight of the NTC thermistor mixture being 100 weight percent, the NTC thermistor mixture may, for example, include 30 weight percent to 45 weight percent of Mn3O4, 25 weight percent to 35 weight percent of Co3O4, and 30 weight percent to 43 weight percent of Ni2O3.

[0024] In other embodiments, in addition to the three element powders, additives may be further added to the NTC thermistor mixture. In these embodiments, based on the total weight of the NTC thermistor mixture being 100 weight percent, the NTC thermistor mixture comprises 30 weight percent to 45 weight percent of Mn3O4, 25 weight percent to 35 weight percent of Co3O4, 30 weight percent to 43 weight percent of Ni2O3, and 0 weight percent to 5 weight percent of additives, wherein the additives comprise iron oxide (Fe3O4), titanium oxide (TiO2), zinc oxide (ZnO), and / or copper oxide (CuO).

[0025] Next, as shown in box 130, the NTC thermistor mixture, 95% toluene and 5% alcohol mixture and oleic acid are mixed, and the NTC thermistor mixture is ball-milled (wet ball-milled) at a rotation speed of 200 to 600 rpm for 4 to 8 hours to obtain a ball-milled mixture. Based on the total weight of the ball-milled mixture as 100 weight percent, the ball-milled mixture contains 40 weight percent to 60 weight percent of the NTC thermistor mixture, 39.5 weight percent to 55 weight percent of the 95% toluene and 5% alcohol mixture, and 0.5 weight percent to 5 weight percent of oleic acid. In some embodiments, the drying temperature of the ball-milled mixture is 100°C.

[0026] Next, the ball-milled mixture is sintered to obtain a NTC thermistor sintered product (also referred to as a thermistor sintered product), as shown in block 140. In some embodiments, the sintering conditions are to increase the temperature to 1000 to 1500° C. within 2 to 5 hours, maintain the temperature for 1 to 3 hours, and then cool naturally to obtain the NTC thermistor sintered product. The sintering can be performed, for example, in an atmosphere of an atmospheric environment.

[0027] After performing block 140, the NTC thermistor sintered material, pinene alcohol and oleic acid amide are mixed to obtain an NTC thermistor sintered material mixture (also referred to as a thermistor sintered material mixture), as shown in block 150. Next, a horizontal ball mill is used to grind the NTC thermistor sintered material mixture at a rotation speed of 800 to 1200 rpm for 3 to 5 hours to ball-mill the NTC thermistor sintered material mixture to obtain an NTC thermistor semi-finished product slurry (also referred to as a thermistor semi-finished product slurry). Based on the total weight of the NTC thermistor sintered material mixture as 100 weight percent, the NTC thermistor sintered material mixture includes 40 weight percent to 60 weight percent of the thermistor sintered material, 40 weight percent to 55 weight percent of pinene alcohol and 0.5 weight percent to 5 weight percent of oleic acid amide.

[0028] In some embodiments, the ball milling slurry comprises adding zirconia beads, SiC, SiO2 or Al2O3. In some embodiments, the diameter of the zirconia beads is 0.5 mm. In some embodiments, the average particle size D50 of the NTC thermistor semi-finished slurry is 0.3 to 0.9 μm.

[0029] After obtaining the above-mentioned NTC thermistor semi-finished product slurry, the NTC thermistor semi-finished product slurry, glass powder and organic carrier are mixed to obtain an NTC thermistor semi-finished product slurry mixture (also referred to as a thermistor semi-finished product slurry mixture). Among them, the organic carrier includes an organic solvent, a binder and an additive. Taking the total weight of the NTC thermistor semi-finished product slurry mixture as 100 weight percent, the NTC thermistor semi-finished product slurry mixture includes 40 weight percent to 70 weight percent of the NTC thermistor semi-finished product slurry, 1 weight percent to 5 weight percent of glass powder, 10 weight percent to 40 weight percent of organic solvent, 5 weight percent to 15 weight percent of binder and 0.5 weight percent to 5 weight percent of additives. It should be noted that the glass powder, organic solvent, binder and additive in the above-mentioned NTC thermistor semi-finished product slurry mixture can be added to the NTC thermistor semi-finished product slurry at one time or in multiple times.

[0030] The addition of glass powder can reduce the sintering temperature of subsequent sintering, which is beneficial to reduce production costs. In some embodiments, the NTC thermistor semi-finished product slurry mixture is stirred and mixed with a planetary mixer.

[0031] After obtaining the NTC thermistor semi-finished slurry mixture, the NTC thermistor semi-finished slurry mixture is rolled using three rollers. Next, the NTC thermistor semi-finished slurry mixture is filtered to obtain the NTC thermistor paste (also referred to as thermistor paste) of the present invention. In some embodiments, after filtering the above-mentioned NTC thermistor semi-finished slurry mixture with 150 mesh, the average grinding fineness of the obtained thermistor paste is less than 20 μm. In some embodiments, the sintering temperature of the NTC thermistor paste is 650°C to 1100°C, for example, below 850°C. In some embodiments, the NTC thermistor paste can be co-fired with the silver paste in an atmosphere of 850°C.

[0032] The present invention provides an NTC thermistor paste. Taking the total weight of the NTC thermistor paste as 100 weight percent, the NTC thermistor paste comprises 50 weight percent to 89 weight percent of NTC thermistor powder (also referred to as thermistor powder), 1 weight percent to 5 weight percent of glass powder, and 10 weight percent to 45 weight percent of an organic carrier. The main component of the NTC thermistor powder is Mn x Co 1-x Ni y O 1.6 , wherein x is 0.4 to 1.0, and y is 0.07 to 0.75. The NTC thermistor powder also contains trace amounts of metal oxides, such as iron oxide, zinc oxide, titanium oxide, copper oxide and / or other metal oxides.

[0033] When the content of NTC thermistor powder is less than 50 weight percent, the electrical characteristics of the thermistor element (e.g., resistance value, reactivity to temperature) will not be as expected. When the content of NTC thermistor powder is greater than 89 weight percent, the paste will not be easy to increase viscosity due to excessive solid powder, which is not conducive to subsequent process processing. When the content of glass powder is less than 1 weight percent, the degree of bonding between the thermistor paste and the substrate will be poor, making it easy to peel off during subsequent processing. When the content of glass powder is greater than 5 weight percent, the electrical characteristics of the thermistor element (e.g., resistance value, reactivity to temperature) will not be as expected. When the content of organic carrier is less than 10 weight percent, the paste will not be easy to increase viscosity due to excessive solid powder, which is not conducive to subsequent process processing. When the content of organic carrier is greater than 45 weight percent, the rheological characteristics of the thermistor paste will be difficult to grasp, which is not conducive to subsequent process processing.

[0034] In some embodiments, the glass powder contains 20 to 50 weight percent of Bi2O3, 10 to 30 weight percent of SiO2, 5 to 30 weight percent of B2O3, 5 to 10 weight percent of TiO2, 5 to 20 weight percent of Al2O3, 5 to 20 weight percent of ZnO, and 5 to 20 weight percent of V2O5, based on the total weight of the glass powder as 100 weight percent.

[0035] Based on the total weight of the organic vehicle being 100 weight percent, the organic solvent comprises 80 weight percent to 92 weight percent of the organic solvent, 5 weight percent to 15 weight percent of the binder, and 3 weight percent to 5 weight percent of the additive.

[0036] When the content of organic solvent is less than 80 weight percent, the wettability of organic solvent to solid powder will be insufficient, or the organic side chain in the binder or additive will not be able to be smoothly moistened, which will cause the dispersion stability of the paste to be insufficient. When the content of organic solvent is greater than 92 weight percent, the solid powder of the paste will not be able to obtain complete dispersion or coating, resulting in poor dispersibility of the paste. When the content of binder is less than 5 weight percent, the viscosity of the paste will be insufficient, which is not conducive to subsequent process processing. When the content of binder is greater than 15 weight percent, the viscosity of the paste will be too high, which is also not conducive to subsequent process processing. When the content of additive is less than 3 weight percent, the paste will produce some abnormalities or difficulties in process processing, such as poor storage dispersibility, bubble generation during process processing, or inability to print or apply on substrate smoothly. When the content of additive is greater than 5 weight percent, it is easy to make the organic side chain in the additive too much entangled with each other, so that the viscosity of the paste is greatly increased, which is not conducive to subsequent process processing.

[0037] In some embodiments, the organic solvent comprises an ester solvent, an alcohol solvent, an aromatic hydrocarbon solvent and / or a petroleum hydrocarbon. In some embodiments, the organic solvent is selected from the group consisting of ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, hexanol, terpineol, benzyl alcohol and petroleum hydrocarbon. In some embodiments, the organic solvent does not comprise methanol and ethanol. Since the NTC thermistor paste of the present case does not comprise methanol and ethanol, it is conducive to long-term storage and is not prone to problems such as deterioration or precipitation.

[0038] In some embodiments, the binder is selected from the group consisting of ethyl cellulose, methyl cellulose, rosin, polymethacrylic acid amine and polyvinyl butyral. In some embodiments, the viscosity of the NTC thermistor paste is 5 Pa·s to 300 Pa·s, such as 50 Pa·s to 280 Pa·s.

[0039] In some embodiments, the additive comprises a dispersant and / or a leveling agent. In some embodiments, the additive is selected from the group consisting of lecithin, oleic acid, stearic acid, fatty acid, erucamide, oleamide, stearic acid amide, polyacrylamide and vinyl bis stearamide. The addition of the additive helps to increase the storage stability of the NTC thermistor paste, reduce the surface tension of the NTC thermistor paste, and increase the dispersibility of the NTC thermistor paste.

[0040] In some embodiments, the resistance temperature coefficient of the NTC thermistor paste is 3900ppm / °C to 4600ppm / °C, such as 4000, 4200, 4400ppm / °C. In some embodiments, the resistivity of the NTC thermistor paste is less than 40Ω·m, such as 1, 10, 20, 25, 30 or 35Ω·m. In some embodiments, the NTC thermistor paste can be applied to a screen printing process, a steel screen printing process or a coating printing process.

[0041] The present invention provides a thermistor paste and a method for making the same. The thermistor paste of the present invention is prepared by mixing a thermistor semi-finished product slurry with glass powder and an organic carrier, wherein the thermistor semi-finished product slurry is sintered, so that the prepared thermistor paste has more uniform electrical properties and better electrical stability. The thermistor paste of the present invention does not contain precious metals such as ruthenium, gold or platinum, so the production cost can be reduced. In addition, the thermistor paste of the present invention can be used in a thick film printing method to quickly produce thermistor interrupter chips.

[0042] Although the present disclosure has been disclosed in the above-mentioned implementation mode, it is not intended to limit the present disclosure. Any person skilled in the art may make various changes and modifications without departing from the spirit and scope of the present disclosure. Therefore, the protection scope of the present disclosure shall be determined by the following claims.

[0043]

Explanation of symbols

[0044] 100: Flowchart

[0045] 110,120,130,140,150: Square frame.

Claims

1. A thermistor paste, characterized in that: Taking the total weight of the thermistor paste as 100 weight percent, it comprises: Thermistor powder, accounting for 50 weight percent to 89 weight percent, wherein the main component of the thermistor powder is Mn x Co 1-x Ni y O 1.6 , x is 0.4 to 1.0, y is 0.07 to 0.75; Glass powder, accounting for 1 weight percent to 5 weight percent; and The organic carrier accounts for 10 weight percent to 45 weight percent, wherein the total weight of the organic carrier is 100 weight percent, and the organic carrier comprises: An organic solvent, accounting for 80 weight percent to 92 weight percent; A binder, accounting for 5 weight percent to 15 weight percent; and Additives, accounting for 3 to 5 weight percent, The average grinding fineness of the thermistor paste is less than 20 μm.

2. The thermistor paste according to claim 1, wherein based on the total weight of the glass powder being 100 weight percent, the glass powder comprises: Bi2O3, accounting for 20 weight percent to 50 weight percent; SiO2, accounting for 10 weight percent to 30 weight percent; B2O3, 5 to 30 weight percent; TiO2, 5 to 10 weight percent; Al2O3, 5 to 20 weight percent; ZnO, 5 weight percent to 20 weight percent; and V2O5, accounting for 5 weight percent to 20 weight percent.

3. The thermistor paste according to claim 1, wherein the organic solvent is selected from the group consisting of ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, hexanol, terpineol, benzyl alcohol and petroleum hydrocarbons.

4. The thermistor paste according to claim 1, wherein the organic solvent does not contain methanol and ethanol.

5. The thermistor paste according to claim 1, wherein the binder is selected from the group consisting of ethyl cellulose, methyl cellulose, rosin, polymethacrylic acid amine and polyvinyl butyral.

6. The thermistor paste according to claim 1, wherein the additive is selected from the group consisting of lecithin, oleic acid, stearic acid, fatty acids, erucamide, oleamide, stearic acid amide, polyacrylamide and vinyl bisstearamide. 7 . The thermistor paste according to claim 1 , wherein the viscosity of the thermistor paste is 5 Pa·s to 300 Pa·s.

8. A method for preparing a thermistor paste, characterized in that: Include: Provide semi-finished thermistor slurry; Provide glass powder; Providing an organic carrier, wherein the organic carrier comprises an organic solvent, a binder and an additive; The semi-finished thermistor slurry, the glass powder and the organic vehicle are mixed to obtain a semi-finished thermistor slurry mixture, wherein the semi-finished thermistor slurry mixture comprises: The semi-finished thermistor slurry accounts for 40 weight percent to 70 weight percent; The glass powder accounts for 1 weight percent to 5 weight percent; The organic solvent accounts for 10 weight percent to 40 weight percent; The binder accounts for 5 weight percent to 15 weight percent; and The additive accounts for 0.5 weight percent to 5 weight percent; and Rolling the thermistor semi-finished product slurry mixture using three rollers; After the thermistor semi-finished product slurry mixture is rolled by three rollers, the thermistor semi-finished product slurry mixture is filtered to obtain the thermistor paste.

9. The method for making thermistor paste according to claim 8, wherein the preparation of the thermistor semi-finished slurry comprises: Providing thermistor sintered materials; Mixing the thermistor sintered material, pineneol and oleamide to obtain a thermistor sintered material mixture, wherein the thermistor sintered material accounts for 40 to 60 weight percent, the pineneol accounts for 40 to 55 weight percent, and the oleamide accounts for 0.5 to 5 weight percent based on the total weight of the thermistor sintered material mixture as 100 weight percent; and The thermistor sintered product mixture is ball-milled to obtain the thermistor semi-finished product slurry. 10 . The method for manufacturing thermistor paste according to claim 8 , wherein the sintering temperature of the thermistor paste is 650° C. to 1100° C.